MORPHOLOGICAL ASPECT IN TRANSLATING THERMODYNAMIC TERMINOLOGY - Farahsani, Yashinta; Harmanto, Margaretha Dharmayanti (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
Several studies on translation have been carried out, namely on the problem of untranslation, translation of terms from various fields, and the formation of target language terms with spelling adjustments. One of them is the field of thermodynamics which is part of the field of Mechanical Engineering, which has many terms borrowed from Dutch and English. Therefore, the researchers are interested in investigating the morphological aspects of the translation of thermodynamic terms using the natural borrowing technique. This study used qualitative research methods. Researchers took terminology data from two books, namely The Fundamental of Engineering Thermodynamics and Fluid Mechanics. The results showed that the forms of borrowing that occurred were (1) borrowing by adjusting spelling and pronunciation adjustments; (2) borrowing with spelling adjustment without pronunciation adjustment; (3) borrowing without spelling adjustment, but with pronunciation adjustment; (4) adjustments to the spelling of prefixes and bound forms found 15 forms of adjustment; (5) suffix spelling adjustments found 20 forms of adjustment; and (6) a combination of translation and borrowing. In short, morphological aspects in translating thermodynamics terms are very important because they relate to the technique used.